ASSESSING THE ROLE OF DIGITAL BANKING IN PROMOTING FINANCIAL INCLUSION IN EMERGING MARKETS - Nida Garnida Fitrianti; Anggun Yolistina; Raden Roro Fatmasari (Organisasi Kreatif Indonesia Emas, 2024)
Background: The dynamic business environment requires organizations to align their strategies with financial insights to remain competitive. Management accounting provides a framework for evaluating business decisions and optimizing resource allocation. Aims: This research aims to investigate the influence of management accounting tools and practices on strategic decision-making and the subsequent effect on organizational performance. Research Method: A mixed-methods approach was adopted, combining quantitative analysis of survey data from 200 organizations with qualitative interviews of senior management professionals. Data were analyzed using statistical tools to identify patterns and relationships. Results and Conclusion: The findings highlight that management accounting significantly supports strategic planning by delivering accurate, relevant, and timely information. Organizations employing advanced management accounting practices demonstrate superior financial performance, enhanced decision-making processes, and a higher capacity to adapt to environmental changes. Contribution: This study bridges the gap between theoretical frameworks and practical applications of management accounting in strategic contexts, offering insights into optimizing resource utilization for organizational success.